산지유통 혁신을 위한 공동마케팅조직 발전전략 - 황의식 (한국농촌경제연구원, 2004)
This study aims to develop strategies for marketing innovation in agricultural producing district in Korea by investigating the introduction of co-marketing firm. The main results of this study are summarized as follows. Firstly, the current situation and problems of marketing in agricultural producing district are examined through the related information and statistics. Secondly, the necessity of introduction of co-marketing firm is discussed. Thirdly, the case studies of overseas on change of marketing organization in foreign agricultural producing district are pursued. Fourthly, the definition of co-marketing firm and selection criteria are directed attention to. Lastly, strategies for developing co-marketing firm are suggested. Researchers: Hwang Eui-Sik, Park Jaehong, Cho Kyung-Chool E-mail address: eshwang@krei.re.kr